Perencanaan Peserta Didik di Smp IT Al-Afkari - Fachruddin Azmi; Mesiono Mesiono; Nur Helmi; Miranti Adelia Afda (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
Management is a science and art to take action to achieve goals. Management of students is one of the management that must be managed properly in educational institutions. Students are people who have the choice to take knowledge in accordance with their aspirations and future hopes. Seeing how important it is for student planning to be carried out in an educational institution, researchers are interested in conducting research to identify and analyze student planning carried out at SMP IT Al Afkari. SMP IT is one of the formal educational institutions that implements the concept of Islamic education based on the Qur'an and Sunnah. Based on the educational concept offered by the IT Middle School, it is not surprising that the IT Middle School is a school that is in great demand because the school is based on religion. The purpose of the research is to analyze the planning of students who are carried out at SMP IT Al Afkari. The type of research used by the author is qualitative research, with descriptive research methods. Student planning carried out at Al Afkari IT Middle School is: an analysis of the needs of students at Al-Afkari IT Middle School is carried out by looking at the number of study rooms in Al-Afkari IT Middle School by adjusting the existing facilities and infrastructure. Student recruitment is carried out in an open system for any student who has graduated from elementary school to continue their education at Al-Afkari IT Middle School, there is no selection of new students. Orientation of students for the introduction of the school environment, as well as class placement according to class level. Keywords: Planning, Students